Parenting Practice, Parental Involvement in School, Child’s Self Concept and School Readiness - Fauziah, Hilda; Hastuti, Dwi; Yuliati, Lilik Noor (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2020)
School readiness before entering primary education is important for children to support future academic achievement. This study aims to identify and analyze parental characteristics, child characteristics, parenting practices, parental involvement in school, self-concept, and school readiness of children aged 5-6 years. This research was conducted in six selected kindergartens at Beji District, Depok City. Total of 100 children and their mothers as respondents who were selected using a convinient sampling method. Data were collected by self-report, observation, and interview methods. Data was analyzed by descriptive analysis using SPSS and influence analysis using smartPLS. The results showed that parenting practices, parental involvement in schools, and the child self concept was categorized is good, and the school readiness of children in categorized was very good. The results of influence analysis show that parenting practices directly influence to parent involvement in school, and the child's self-concept. Parenting practices also indirectly influence school readiness through the involvement of parents in the school. The other results show that parenting practices and parent involvement in schools directly influence significant positive on school readiness. Meanwhile, children's self-concept has no effect to school readiness. Overall parenting practice and parent involvement in school very important role of increasing children's school readiness. In the other hand, it’s necessary synergism between home and school environment to optimize child's self concept.